NONLINEAR SYSTEM ANALYSIS OF A 87SR/86SR TIME SERIES FOR PHANEROZOIC SEAWATER - Podlaha O.G.; Chalimourda A.; Albeverio S. (My University, 1999)
In this paper we investigate the presence of chaos in the system that underlies the Phanerozoic 87Sr/86Sr isotope record of seawater carbonates by means of nonlinear time series analysis. The Fourier power spectrum estimation from the original time series together with the geological conjecture that the system is controlled only by a few (2 to 4) degrees of freedom point to an underlying chaotic system. The zero-order, correlation dimension and the largest Lyapunov exponent methods are employed to prove or to reject this assumption. Inherent problems of the data sets (non-equidistant and too sparse for a reliable application of these techniques) and the inability of the currently available methods to cope with them do not yet allow for a clear-cut decision.
Keywords: PHANEROZOIC; JURASSIC; CHAOS; TIME SERIES ANALYSIS; Мезозой::Юрская; Mesozoic::Jurassic